Early prenatal ultrasonographic diagnosis and follow up treatment of a giant abdominal hemangioma: a rare case report - Dinu-Florin Albu; Cristina-Crenguta Albu; Andrei Oncescu; Stefan-Dimitrie Albu (International Journal of Medical Research and Review, 2016)
We report the rare case of a fetus diagnosed in utero as early as 16 weeks with a growing lateral abdominal wall hemangioma. Ultrasonography confirms space occupying lesion and Colour Doppler ultrasound examination proves the vascularity of lesion. Fetal MRI was performed at 27 weeks and confirmed the localization, neither of the internal organs being affected and no other hemangiomas being detected. The baby was delivered at 36 weeks after premature rupture of membranes and transferred to the pediatric department. Angiography was performed and after further analysis the baby was referred for surgical treatment. Surgery was a success and the baby came for the routine 6 months check up.